Parameter Pertumbuhan (L∞, K , T0) dan Tingkat Kematangan Gonad Ikan Cakalang Katsuwonus pelamis - soukotta, imanuel vt; Saputra, Suradi Wijaya (Prodi Ilmu Kelautan Fakultas Perikanan dan Ilmu Kelautan Universitas Pattimura, 2023)
This research was conducted to determine growth patterns and gonadal maturity levels, samples were taken randomly when the fishermen unloaded the fish from the boat. The results showed that skipjack tuna (Katsuwonus pelamis) obtained a growth coefficient (K) of 1.85 per year with an asymptotic length of 75.90 cm, t0 -0.06501 years with T max maximum age = 3/K+t0 of 1 .5 years and an Rn value of 0.169. After plugging the growth value into the von Bertalanffy equation for skipjack tuna caught in the Banda seas of Maluku Province, the equation Lt=75.901-e-0.14(t+0.06501) for skipjack tuna caught in Banda Sea waters. Visually, the results of observations in the field showed that female skipjack tuna entered TKG II at body length 44-59 cm, gonad length was 17.4 cm and male skipjack tuna reached TKG II at body length 43-58 cm, gonad length was 16.5 cm. The results showed that entering TKG III visually at body length measures 50.5-73.5 with a gonad length of 20 cm for female skipjack tuna and male skipjack tuna for TKG III dominates with a body length size of 70.5-79.5 cm with a gonad length of 20 cm